From Motivation to Demotivation to Remotivation: Motivational Fluctuations in EFL Classrooms - Kiehelä, Alina (My University, 2021)
This thesis investigates demotivation and remotivation in EFL learning to find the factors causing demotivation among EFL learners and the efficient remotivational strategies in overcoming demotivation. The thesis offers a theoretical overview of the main currents in L2 motivation research and broadens the concept with the further investigation of demotivation and remotivation. The main references within the field of motivation are to Robert Gardner and Wallace Lambert, Edward Deci and Richard Ryan, and Zoltán Dörnyei. Concerning demotivation, the thesis draws in research studies investigating the demotivational factors experienced in different EFL contexts. The researchers in this field include Keita Kikuchi, Tae-Young Kim and Zoltán Dörnyei. Regarding remotivation, multiple studies investigating the remotivational factors helping overcome demotivation are presented. The researchers of this topic include Joseph Falout, Christopher Carpenter, Ema Ushioda, and others. The meta-analysis showed variance between factors causing demotivation in different learning environments and cultures. The most common demotivational factors were teacher variables, course contents and teaching materials, and negative attitudes toward learning English. Data showed strong demotivation until high school, but lower again in college. Most of the efficient remotivational strategies were internal to the learner, such as a change in perspective, although situation-specific and social factors were significant too. Some suggestions were made concerning the exact strategies EFL teachers could use to promote the learners’ remotivation. Further research should investigate the efficiency of specific remotivational strategies to overcome demotivation among EFL learners. In addition, research should be conducted to examine the remotivational factors in Finland.
Keywords: Language acquisition, foreign languages, motivation (mental objects), motivation (activity), study motivation, learning, language learning, language teachers, second language